SIRT1 Undergoes Alternative Splicing in a Novel Auto-Regulatory Loop with p53 - Lynch, Cian J.; Shah, Zahid H.; Allison, Simon J.; Ahmed, Shafiq U.; Ford, Jack; Warnock, Lorna J.; Li, Han; Serrano, Manuel; Milner, Jo (PLOS ONE, 2010)
Background The NAD-dependent deacetylase SIRT1 is a nutrient-sensitive coordinator of stress-tolerance, multiple homeostatic processes and healthspan, while p53 is a stress-responsive transcription factor and our paramount tumour suppressor. Thus, SIRT1-mediated inhibition of p53 has been identified as a key node in the common biology of cancer, metabolism, development and ageing. However, precisely how SIRT1 integrates such diverse processes remains to be elucidated. Methodology/Principal Findings Here we report that SIRT1 is alternatively spliced in mammals, generating a novel SIRT1 isoform: SIRT1-ΔExon8. We show that SIRT1-ΔExon8 is expressed widely throughout normal human and mouse tissues, suggesting evolutionary conservation and critical function. Further studies demonstrate that the SIRT1-ΔExon8 isoform retains minimal deacetylase activity and exhibits distinct stress sensitivity, RNA/protein stability, and protein-protein interactions compared to classical SIRT1-Full-Length (SIRT1-FL). We also identify an auto-regulatory loop whereby SIRT1-ΔExon8 can regulate p53, while in reciprocal p53 can influence SIRT1 splice variation. Conclusions/Significance We characterize the first alternative isoform of SIRT1 and demonstrate its evolutionary conservation in mammalian tissues. The results also reveal a new level of inter-dependency between p53 and SIRT1, two master regulators of multiple phenomena. Thus, previously-attributed SIRT1 functions may in fact be distributed between SIRT1 isoforms, with important implications for SIRT1 functional studies and the current search for SIRT1-activating therapeutics to combat age-related decline.